Grammatical Interference in English Language Acquisition: A Comparative Study of Uzbek and Russian Learners (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The current paper examines grammatical interference as a significant factor influencing foreign language acquisition (FLA), focusing on Uzbek and Russian learners of English. We analyze how syntactic and morphological structures of learner’s first language (L1) affects foreign language production and comprehension. Based on comparative linguistic analysis, we try to highlight repeated grammatical errors and mistakes that stem from the differences in word order, article usage, verb aspects, and prepositions. Particularly, we emphasize such structural features of Uzbek and Russian as agglutination, free word order, postpositions, gender, and inflections, which often conflict with English grammatical norms. The findings underscore the necessity to raise learners’ grammatical awareness in order to foster accurate and fluent English language use.